Digital Marketing Sebagai Upaya meningkatan Usaha di Anugerah Wira Angkasa - Khoirul Anwar (AL-MANSYUR: Jurnal Ekonomi Syariah, 2025)
This study examines the impact of implementing digital marketing on business growth at Anugerah Wira Angkasa, particularly in the post-pandemic era of COVID-19, which has restricted face-to-face interactions. Using a qualitative case study approach, this research analyses digital marketing strategies through social media, particularly Instagram, and their impact on increasing student numbers and enhancing brand awareness. The results of the study indicate that digital marketing offers various advantages over conventional strategies, such as cost-effectiveness, broader reach, faster branding processes, and significant opportunities for sales growth. Anugerah Wira Angkasa successfully increased its social media followers from 1,500 in 2020 to 4,500 in 2025, contributing to increased business volume and interest from prospective students. Key factors in the success of digital marketing include selecting the right platform, content quality, consistency in posting, and understanding social media algorithms. Thus, digital marketing has proven to be an important strategy for enhancing competitiveness, ensuring business sustainability, and aligning with Islamic values that promote productivity and innovation.